Job Training and Employee Performance: Evidence from the Incoming Quality Control Department of PT XYZ - Kinanti Mangestisari; Agung Surya Dwianto (Jurnal Relevansi : Ekonomi, Manajemen dan Bisnis, 2026)
This study examined the effect of job training on employee performance in the Incoming Quality Control (IQC) department of PT XYZ, where inspection accuracy is essential for maintaining product quality and operational efficiency. A quantitative approach was used, with data collected from 50 IQC employees through a structured questionnaire. The data were analyzed using validity and reliability tests, as well as simple linear regression in SPSS version 25. The findings indicated that job training had a positive and statistically significant effect on employee performance. Improvements were observed in productivity, work quality, timeliness, and cycle time efficiency. These results emphasize the important role of training in improving employee competencies and supporting effective quality control. This study is limited to a single department with a relatively small sample size, which may affect the generalizability of the findings. This study provides empirical evidence that job training is a strategic investment in human resource development in manufacturing organizations.